2020
DOI: 10.4103/jfmpc.jfmpc_1071_19
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tobacco consumption on periodontal health: A stratified analysis based on type of tobacco use

Abstract: Introduction: Though the negative influence of tobacco consumption on the periodontal status of an individual is established, the magnitude of this association based on the type of tobacco used is seldom investigated. Aim: The aim of this study is to check the differences in the periodontal status of individuals based on their current tobacco consumption status and type of tobacco consumption. Materials and Methods: This study was conducted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…The CAL and PPD increased with the duration of the mishri use in our study which was statistically significant. The results of our study are similar to previous studies, where they found progressive destruction of periodontal tissues in SLT users [30][31][32].…”
Section: Resultssupporting
confidence: 92%
“…The CAL and PPD increased with the duration of the mishri use in our study which was statistically significant. The results of our study are similar to previous studies, where they found progressive destruction of periodontal tissues in SLT users [30][31][32].…”
Section: Resultssupporting
confidence: 92%
“…Among the participants consuming paan, 105 (44.9%) of them had 4-5 mm of the periodontal pocket, and 97 (41.5%) participants had 6 or more mm of the periodontal pocket. This result was in conformity with another study conducted by Yaragani A et al [ 15 ] In the survey conducted by Muthukrishnan A et al [ 16 ] 65.7% of the subjects showed periodontal loss of attachment which showed similar results to our study. The finding of the current investigation was comparable to those of the survey carried out by Kumar G et al [ 10 ] Niaz K et al [ 17 ]…”
Section: Discussionsupporting
confidence: 93%
“…More alarming is the acquisition of tobacco chewing patterns in various ways. In the research done by Yaragani et al [15], 82% of current tobacco consumers were found although, 49% reported smoking tobacco, they had tobacco chewing habits. These estimates are in line with details from the Global Adult Tobacco Survey 2016-17 [16,17].…”
Section: Resultsmentioning
confidence: 92%